The mysteries of the Bermuda Triangle - Belanger, Jeff (All aboard reading., 2010)
Supernatural investigator Jeff Belanger provides information about the Bermuda Triangle, discussing how many ships have been lost in the area, why it is such a mystery, and other related topics.